Ubiquitin is Associated with Early Truncation of Tau Protein at Aspartic Acid(421) during the Maturation of Neurofibrillary Tangles in Alzheimer's Disease - García‐Sierra, Francisco (Brain Pathol, 2011)
Pathological processing of tau protein during the formation and maturation of neurofibrillary tangles (NFTs) includes abnormal phosphorylation, conformational changes and truncation of the C‐terminus at aspartic‐acid(421) (apoptotic product) and glutamic‐acid(391) residues. Abnormal phosphorylation and misfolding may serve as recognition signals for ubiquitin‐targeting and proteosomal processing. For this reason, we sought to determine whether ubiquitin‐targeting of tau is associated with particular tau modifications that herald specific stages of NFTs maturation in the hippocampus of Alzheimer's disease cases. Using multiple tau antibodies, we found that 30% of the total load of NFTs is ubiquitin‐associated. As reported previously ubiquitin immunoreactivity was associated with markers of phosphorylated tau in certain NFTs; however, a strong association was also found between ubiquitin and the earliest known truncation event at aspartic‐acid(421). These findings indicate that tau protein in the NFTs may be dually subjected to both apoptotic and proteosomal processing. By contrast ubiquitin immunoreactivity was poorly associated with truncation of tau at glutamic‐acid(391), suggesting that this proteolytic event may be independent of proteosomal activity. It would appear, therefore, that ubiquitin targeting of tau protein occurs at NFTs in the early and intermediate stages of the maturation.